A Novel Forceps for Preventing Mucosal Damage of the Hard Palate in Maxilla Mobilization During Le Fort I Osteotomy. Issue 8 (30th November 2022) - Chen, Kai; Sun, Xiumei; Wu, Guomin
Abstract : At present, the most effective and common strategy to mobilize the maxilla is to use Rowe disimpaction forceps. But because of the directed forces on the hard palate, the mucosa of the hard palate will have to receive an ineluctable mechanical injury. Therefore, we introduce a novel forceps (Patent No. 202110966069.X China), which can accurately and steadily clamp the maxilla on the premise of protecting the hard palate mucosa from loss of palatal vascularity and pressure necrosis, and then thoroughly mobilize the maxilla. Complaints and mucosal damage were not observed in the initial 3 patients.